Analisis Kesalahan Penggunaan Ejaan yang disempurnakan Edisi V pada Penulisan Karya Ilmiah Mahasiswa Stikes Nani Hasanuddin Makassar - Husni Bt Salam; Nurfaedah Ririn; Indraswari Indraswari (Journal on Education, 2023)
One of the written works that pays attention to linguistic rules is papers. However, there are still many errors in the use of language in writing papers by students. This study aims to find out the form of language errors in writing papers in health students in the fifth semester of 2021 at Stikes Nani Hasanudin Makassar. This research uses descriptive qualitative method. The focus of the research is language errors in spelling, choice of words and effective sentences. The data collection technique used is the method of taking notes from paper documents with a sample of 30 student papers. The results of this study indicate that there are 272 language errors in 30 papers by STIKES NANI Hasanuddin Makassar students. Spelling errors were 80.9%, word choice errors were 8.45%, and effective sentence formulation errors were 10.65%. The conclusion of this study is that there are still many language errors in writing papers made by students because of the lack of student knowledge about using good and correct language in writing papers.